Effect of Ultraviolet Radiation on Pathogenity of White Spot Syndrome Virus in Giant Tiger Prawn (Penaeus monodon Fab.) - Subkhan, M.; Alifuddin, M.; Taslihan, A. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This experiment was conducted to examine the effect of UV irradiation on pathogenity of white spot syndrome virus (WSSV) in black tiger shrimp (Penaeus monodon Fab.). A hundred ml of WSSV virus suspension (200 μg/ml) were placed at 30 cm under UV light 10 Watt. Radiation on WSSV virus was performed for 15, 30, 45, and 60 minutes. Black tiger sjrimp in density of 260 tails/L were immersed in 1000 ml of irradiated virus suspension (20 μg/ml) to test their pathogenities. The results of study showed that duration of UV irradiation on WSSV virus was reverse correlated to their pathogenities. In constrast, survival of black tiger shrimp was linear correlated to duration of UV inactivation of virus. Higher survival rate of shrimp (65.52%) after challenge test was obtained by irradiation of virus for 60 min. Keywords: WSSV, virus, pathogen, ultraviolet, black tiger prawn, Penaeus monodon ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh radiasi UV terhadap patogenitas virus White Spot Syndrome Virus (WSSV) pada udang windu (Penaeus monodon Fab). Suspensi virus WSSV dengan konsentrasi 200 μg/ml sebanyak 100 ml ditempatkan 30 cm diradiasi menggunakan UV 10 Watt. Radiasi dilakukan selama 15, 30, 45, dan 60 menit. Udang dengan kepadatan 260 ekor/L direndam dalam 1000 ml suspensi virus (20 μg/ml) hasil radiasi untuk menguji patogenitasnya. Hasil penelitian menunjukkan bahwa lama radiasi UV pada virus WSSV berbanding terbalik dengan tingkat patogenitasnya. Sementara itu, lama inaktivasi virus dengan UV berbanding lurus terhadap kelangsungan hidup udang. Kelangsungan hidup udang windu tertinggi (65,52%) setelah uji tantang diperoleh dengan meradiasi virus selama 60 menit. Kata kunci: WSSV, virus, patogen, ultraviolet, udang windu, Penaeus monodon